Study the Effect of Caspase-3, Lactate Dehydrogenase, and Oxidative Stress Levels as Promising Biomarkers to Mediate Colon Cancer Therapy - Mowat, Ashwaq N.; Al-Abady, Zainab N. (Journal of Biomedicine and Biochemistry, 2024)
Background Colon cancer is a global health concern prevalent in low- income countries. Its progression is linked to oxidative stress, apoptosis, and metabolic changes.Aim This study aims to evaluate the diagnostic and prognostic signif- icance of lactate dehydrogenase (LDH) and caspase-3 (CASP3) in colon cancer patients, alongside assessing oxidative and antioxidative markers such as malondialdehyde (MDA) and catalase activity (CAT).Materials and Methods The study included 20 colon cancer patients and 20 healthy controls (9 males and 11 females). Serum levels of LDH and CASP3 were measured using the ELISA technique, while MDA and CAT levels were determined spectrophotometrically.Results Colon cancer patients exhibited significantly higher levels of LDH, CASP3, and MDA compared to healthy controls, indicating in- creased metabolic activity, apoptosis, and oxidative stress. Conversely, CAT activity was significantly reduced in patients, suggesting impaired antioxidant defenses. Elevated LDH levels correlated with tumor stage, size, and cell differentiation, influencing disease-free and overall survival. CASP3 levels also showed potential as a diagnostic biomarker for colorec- tal cancer. MDA levels reflected oxidative damage, while CAT reduction indicated disruption in the oxidant-antioxidant balance.Conclusion This study highlights LDH and CASP3 as valuable diag- nostic and prognostic biomarkers, with MDA and CAT providing addi- tional insights into oxidative stress in colon cancer. These biomarkers could serve as potential therapeutic targets, aiding disease management and treatment strategies.